Peran Komunikasi Ibnu Rusyd Dalam Peradaban Islam diEropa - Al Ghifari, Muhammad Shiddiq (Sadida: Islamic Communications and Media Studies, 2024)
The spectacular progress of Islamic civilization in the West cannot be separated from the role of communication and Muslim philosophers who existed in the Middle Ages. In this century, Islam became a spearhead in scientific civilization. Ibn Rushd was a Muslim philosopher who had a very important role in the development of Islam in Europe, but the influence of Ibn Rushd himself did not occur in the mass of his life, but through his students who loved his thoughts, so that these students translated his works into Latin and this is called Aveoroism. Aveorism itself has a point of view on the relationship between philosophy and religion, and this view is based on Ibn Rushd. With his abilities, Ibn Rushd succeeded in commenting on the works of Aristotle, and gave rise to a culture of thought that had never been experienced in that period of civilization. Ibn Rushd's thoughts had a lot of influence on other philosophers. And he is considered the most influential and instrumental figure in Islamic civilization in the western world. Therefore, studying his life journey and philosophical thoughts is very interesting.